Die amerikanische Krankheit : Vier Lektionen der Freiheit aus einem US-Hospital - Snyder, Timothy (Beck Paperback., 2020)
"From the author of On Tyranny comes an urgent diagnosis of an American malady: our heartless system of commercial medicine and our politics of pain. On December 29, 2019, historian Timothy Snyder fell gravely ill. Unable to stand, barely able to think, he waited for hours in an emergency room before being correctly diagnosed and rushed into surgery. Over the next few days, as he clung to life and the first light of a new year came through his window, he found himself reflecting on the fragility of health, not recognized in America as a human right, but without which all rights and freedoms have no meaning. And he had no idea how much worse things could get. Now, American hospitals, long understaffed and undersupplied, are buckling under waves of coronavirus patients. The federal government has responded with willful ignorance, misinformation, and profiteering. Even with public life at a standstill, thousands of Americans continue to die, needlessly, every single day. In this eye-opening cri de coeur, Snyder traces the societal forces that led us here and outlines the lessons we must learn to survive. In examining some of the darkest moments of recent history and of his own life, Snyder finds glimmers of hope, and principles that could lead us out of our current malaise. Only by enshrining healthcare as a human right, elevating the authority of doctors and medical knowledge, and planning for our children's future can we create an America where everyone is truly free"--